2015
DOI: 10.1167/15.6.17
|View full text |Cite
|
Sign up to set email alerts
|

The role of sensory ocular dominance on through-focus visual performance in monovision presbyopia corrections

Abstract: Monovision presbyopia interventions exploit the binocular nature of the visual system by independently manipulating the optical properties of the two eyes. It is unclear, however, how individual variations in ocular dominance affect visual function in monovision corrections. Here, we examined the impact of sensory ocular dominance on visual performance in both traditional and modified monovision presbyopic corrections. We recently developed a binocular adaptive optics vision simulator to correct subjects' nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 55 publications
2
27
1
Order By: Relevance
“…We surmise that this slight bias toward left-eye dominance might be related to the disparity in mean luminance between left-and right-eye LCOS displays, discovered after the fact. Three earlier rivalry studies reporting eye dominance results did not observe this trend toward left-eye dominance (Ooi & He, 2001;Al-Dossari et al, 2015;Zheleznyak et al, 2015).…”
Section: Resultsmentioning
confidence: 83%
“…We surmise that this slight bias toward left-eye dominance might be related to the disparity in mean luminance between left-and right-eye LCOS displays, discovered after the fact. Three earlier rivalry studies reporting eye dominance results did not observe this trend toward left-eye dominance (Ooi & He, 2001;Al-Dossari et al, 2015;Zheleznyak et al, 2015).…”
Section: Resultsmentioning
confidence: 83%
“…Such tests are tapping into sensory-motor aspects of vision; they are not purely sensory in nature. Still, some previous studies using extended binocular rivalry tracking have found a link between sighting eye dominance and SED (Bosten, Goodbourn, Lawrance-Own, Bargary, Hogg & Mollon, 2015, Handa et al, 2004, Porac & Coren, 1978, Zheleznyak et al, 2015). However, we found no such relationship between measures in our data (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…To account for all possible means through which a dominant eye might gain disproportionate predominance (see Fig. 1), and for the sake of consistency with previous studies that measured SED in prolonged binocular rivalry tracking blocks (Handa et al, 2004, Porac & Coren, 1978, Zheleznyak et al, 2015), we compared various aspects of rivalry dynamics to a metric of SED based on overall differences in predominance between the LE and RE (see 2.5 Data Analysis ). This metric (which we call SED) ranges from −100% (complete LE predominance) to +100% (complete RE predominance), and reflects the difference in the proportion of exclusive visibility of the RE and LE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations